منظومہ اصول الفقہ: علامہ ابن الشحنہ اور منظومہ کا تعارفی مطالعہ: (Manzooma–E-Usool–Ul-Fiqh: An Introductory Study of Allama Ibn al-Shihna and the Poem) - Amin Ullah; Dr. Hafiz Tahir Islam Askari (Al Manhal Research Journal, 2025)
The knowledge of Usul al-Fiqh (Principles of Islamic Jurisprudence) holds great importance in deriving the rulings of Sharia. Through this knowledge, not only are the issues that are not explicitly mentioned in the Quran and Hadith addressed, but also those issues introduced by the modern world are resolved. Scholars of Usul al-Fiqh have made significant contributions and provided Islamic libraries with a vast collection of works. Scholars from each school of thought have written books on their respective principles, and later scholars have conducted research on these books. Just as in other sciences, alongside prose works, poetic compositions have also been produced, in the field of Usul al-Fiqh, many poetic works have been written. In addition to the Hanafi school , the principles of other schools have also been compiled in poetic form. For example, the famous poem of Imam al-Shanqiti, "Maraq al-Su‘ud limubtaghi al-ruqqi wa al-suud," explains the Maliki principles. In Hanafi Usul al-Fiqh, a poetic work titled "Al-Kawakib" was written by Imam Muhammad al-Kawakibi, which was later researched by Mahmood Askar. In short, all fields have benefited from poetic works, and research, compilation, and categorization of these poems have been carried out, with relevant experts making use of these works. One of the brief and comprehensive poetic works in the field of Usul al-Fiqh is the one written by Imam Abu al-Walid Muhammad ibn Muhammad, known as Ibn al-Shihna (d. 815 AH). Imam Ibn al-Shihna, in addition to several other works, composed poems in various sciences. One such work is his "Alfiyyat al-Rajaz," which covers topics related to Tafsir, Fiqh, Usul al-Fiqh, and other sciences. The poem under discussion is part of this Alfiyyah and consists of 101 verses, in which the basic discussions of Hanafi Usul al-Fiqh are comprehensively presented.